IL-1β-Induced Matrix Metalloprotease-1 Promotes Mesenchymal Stem Cell Migration via PAR1 and G-Protein-Coupled Signaling Pathway - Ming-Siou Chen; Cheng-Yu Lin; Yun-Hsuan Chiu; Chie-Pein Chen; Pei-Jiun Tsai; Hwai-Shi Wang (Stem Cells International)
Mesenchymal stem cells (MSCs) are known for homing to sites of injury in response to signals of cellular damage. However, the mechanisms of how cytokines recruit stem cells to target tissue are still unclear. In this study, we found that the proinflammation cytokine interleukin-1β (IL-1β) promotes mesenchymal stem cell migration. The cDNA microarray data show that IL-1β induces matrix metalloproteinase-1 (MMP-1) expression. We then used quantitative real-time PCR and MMP-1 ELISA to verify the results. MMP-1 siRNA transfected MSCs, and MSC pretreatment with IL-1β inhibitor interleukin-1 receptor antagonist (IL-1RA), MMP tissue inhibitor of metalloproteinase 1 (TIMP1), tissue inhibitor of metalloproteinase 2 (TIMP2), MMP-1 inhibitor GM6001, and protease-activated receptor 1 (PAR1) inhibitor SCH79797 confirms that PAR1 protein signaling pathway leads to IL-1β-induced cell migration. In conclusion, IL-1β promotes the secretion of MMP-1, which then activates the PAR1 and G-protein-coupled signal pathways to promote mesenchymal stem cell migration.